Methane concentrations in headspace gas prepared from shallow sediment core GeoB22031-1 collected with a multicorer off South Georgia, Southern Ocean, R/V METEOR cruise M134/1 - Thomas Pape; Janice Malnati; Gerhard Bohrmann (PANGAEA, 2025)
Shallow sediment cores were collected with a MultiCorer at locations on the shelf and slope of South Georgia during cruise M134/1 with R/V METEOR in 2017. In order to determine distributions of methane and characterize biogeochemical zonations in the sediment, 3 mL of the sediment was removed from the cores at defined depths using cut-off syringes and transferred to 20 mL glass vials filled with 5 ml NaOH solution to generate a 12 mL headspace gas volume. The headspace gas samples were analyzed for their methane concentrations by use of a gas chromatograph equipped with a capillary column and a flame ionization detector.